2012
DOI: 10.1155/2012/429108
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Disorders of Consciousness

Abstract: Objectives. To determine the severity of stroke and mortality in relation to the type of disturbance of consciousness and outcome of patients with disorders of consciousness. Patients and Methods. We retrospectively analyzed 201 patients. Assessment of disorders of consciousness is performed by Glasgow Coma Scale (Teasdale and Jennet, 1974) and the Diagnostic and Statistical Manual of Mental Disorders (Anonymous, 2000). The severity of stroke was determined by National Institutes of Health Stroke Scale (Lyden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
1
8
0
1
Order By: Relevance
“…This was in agreement with previous studies [26,30]. However, this was in disagreement with other studies that found delirium was significantly less prevalent in hypertensive patients [18] and smokers [28] and higher among stroke patients with cardiac disease [5].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This was in agreement with previous studies [26,30]. However, this was in disagreement with other studies that found delirium was significantly less prevalent in hypertensive patients [18] and smokers [28] and higher among stroke patients with cardiac disease [5].…”
Section: Discussionsupporting
confidence: 74%
“…Delirium is a multifactorial neuropsychiatric disorder with definite predisposing and precipitating factor [18] and is one of the most common complications that older patients develop affecting up to 30% of all older medical hospitalized patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] An especially challenging clinical conundrum is in the management of patients with disorders of consciousness after brain injury given their inability to participate in crucial neurorehabilitation. [8][9][10] Disorders of consciousness may include minimally conscious or vegetative states that can persist from months to years after the initial insult. [8][9][10] These disorders of consciousness are associated with a high degree of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced level of consciousness may also be a direct consequence of strokes particularly of the thalamus or the brainstem [25]. Previous studies found the prevalence of impaired consciousness to range between 5 and 40%, depending on the timing of assessment after stroke [26][27][28][29][30]. Delirium which affects relevant proportions of stroke patients [31], may also impact on language use and hence substantially interfere with successful communication [32].…”
Section: Introductionmentioning
confidence: 99%